Deep Submarine Giant Scours in northern Gulf of Cadiz (offshore SW Iberia) : a singular case of sedimentary and tectonic coupling - Duarte, João C. (2015)
European Geosciences Union General Assembly 2007 (EGU 2007), Vienna, Austria, 15-20 April 2007